Valorization of avocado peel waste: extraction and characterization of cellulose nanofibers for multifunctional applications - Varsha, P. V.; Neenu, K. V.; Begum, P. M. Sabura; Hounfodji, Jean Wilfried; Sankar, Sameera; Muraleedharan, Sneha; Kamath, Anjali N.; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Midhun, Dominic C. D. (Biomass Conversion and Biorefinery, 2025)
This study explored the utility of underutilized avocado peels for extracting cellulose nanofibers (CNFs). Mild oxalic acid hydrolysis assisted by steam explosion was employed after alkali hydrolysis and chlorine-free bleaching to prepare cellulose nanofibers. The structural, atomic, and elemental features of the extracted fibers were studied using Fourier transform infrared spectroscopy (FTIR), 13C solid-state nuclear magnetic resonance (13C NMR) spectroscopy, and energy dispersive X-ray (EDAX) analysis, respectively. The crystallinity index of the nanofibers was 87%, which was 53% greater than that of the crude sample. The elution of hemicellulose and lignin was evident from the scanning electron microscopy (SEM) images, and the nanofibers had a fiber diameter of 30–82 nm according to the transmission electron microscopy (TEM) analysis. The applied chemical treatment also elevated the thermal stability of the fibers. The extracted fibers can be applied in numerous fields, including electronics, packaging, automobiles, biomedicine, and cosmetics.